Genetics of the estuarine copepod Eurytemora affinis with regard to improving water quality. (5th November 2020) - Minguez, Jérémy; Maris, Tom; Tackx, Micky; Gers, Charles; Meire, Patrick; Legal, Luc
Abstract: As an estuary being restored, the Scheldt (Belgium/The Netherlands) offers an interesting setting to study the response of organisms and ecosystems to changing conditions. In this regard, this study specifically deals with the spatio-temporal distribution and possible genetic differentiation among the species complex Eurytemora affinis (Copepoda, Calanoida). Until the 1990s, E. affinis typically occurred downstream the estuary. In parallel to water quality improvement, E. affinis since recently also occurs upstream in the estuary and in some of the tributaries. In a former study, Gasmi et al. (2014), found little genetic differentiation between the upstream population and downstream one, which is probably at the origin of the upstream population. However, surprisingly, two different genetic entities of the E. affinis complex were present: one in the main stream of the Scheldt estuary and one in its tributaries. This present work aims at understanding how independent tributaries, situated at opposite sides of the estuary, can host a single genetic entity while another one is present only in the main estuary. A dense sampling in the main stream and the two main tributaries was made in May 2014 (12 locations) and four ISSR primers producing 78 polymorphic loci were used to perform a molecular analysis. Bayesian and hierarchical analysis revealed that the results are more mixed and the different genetic entities are less well delimited than reported in our former study based on samples collected in 2012. A genetical mix between tributary and upstream populations is now observed. This suggests that a homogenization process of the E. affinis populations is in progress in parallel to the improvement of water quality. These results are discussed and several explanations are proposed. Highlights: Molecular diversity of Eurytemora affinis . Fast genetic changes in populations of the species complex Eurytemora affinis . Spatio-distribution of E. affinis genotypes in parallel to an estuary restoration process.